Presidential welcome address – SA Heart® Congress 2025 - Mpe, Martin (SA Heart Journal, 2025)
It is both a great honour and a personal privilege to welcome you to the 25th Annual SA Heart® Congress, a landmark event in our history. This year, we proudly celebrate a quarter century of cardiovascular excellence; 25 years of advancing heart health, scientific innovation, and professional collaboration across South Africa and beyond.